Westonci.ca is the ultimate Q&A platform, offering detailed and reliable answers from a knowledgeable community. Get detailed and accurate answers to your questions from a dedicated community of experts on our Q&A platform. Explore comprehensive solutions to your questions from knowledgeable professionals across various fields on our platform.
Sagot :
Answer:
f⁻¹(x) = (x + 10)/2
General Formulas and Concepts:
Algebra I
- Equality Properties
- Inverse Functions
Step-by-step explanation:
Step 1: Define
f(x) = 2x - 10
Step 2: Rewrite
- Redefine: y = 2x - 10
- Swap x/y: x = 2y - 10
Step 3: Find Inverse
Solve for the new y.
- Add 10 to both sides: x + 10 = 2y
- Divide 2 on both sides: (x + 10)/2 = y
- Rewrite: y = (x + 10)/2
- Redefine: f⁻¹(x) = (x + 10)/2
Answer:
[tex]let \: the \: {f}^{ - 1}(x) \: be \: m \\ m = \frac{1}{2x - 10} \\ m(2x - 10) = 1 \\ 2x - 10 = \frac{1}{m} \\ x = \frac{1}{2m} + 5 \\ therefore \\ {f}^{ - 1} (x) = \frac{1}{2x} + 5[/tex]
Thanks for stopping by. We are committed to providing the best answers for all your questions. See you again soon. Thank you for visiting. Our goal is to provide the most accurate answers for all your informational needs. Come back soon. Thank you for trusting Westonci.ca. Don't forget to revisit us for more accurate and insightful answers.